2014
DOI: 10.1016/j.foodres.2014.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and quantification of saponins: A review

Abstract: Saponins, a second metabolites mainly derived from plant materials, have been used extensively in drug-related industry due to the pharmaceutical properties. These have driven the emergence of various new extraction technologies with the main purpose to optimize the yield in order to accommodate the recent need. The plants containing saponins are discussed, and their pharmaceutical properties and applications in food are highlighted. This review focuses on the saponin extraction with emphasis on conventional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
229
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(274 citation statements)
references
References 166 publications
5
229
0
12
Order By: Relevance
“…However, the three water-based extractions were better than all the organic solvent extractions tested and the TPC for the MAE was 2.2 times higher than for the best of the alcoholic extractions tested, 70% methanol (Figure 3). These findings suggest that the extractable Due to their amphiphylic nature, saponins are usually extracted with water or alcohols using many different techniques [13,38]. The present results indicate that the Gac seed saponins are more soluble in alcohols than in water (Figure 2), which is consistent with these saponins being triterpenoids [8,9].…”
Section: Effect Of Extraction Methods On Total Phenolic Content (Tpc)supporting
confidence: 75%
See 2 more Smart Citations
“…However, the three water-based extractions were better than all the organic solvent extractions tested and the TPC for the MAE was 2.2 times higher than for the best of the alcoholic extractions tested, 70% methanol (Figure 3). These findings suggest that the extractable Due to their amphiphylic nature, saponins are usually extracted with water or alcohols using many different techniques [13,38]. The present results indicate that the Gac seed saponins are more soluble in alcohols than in water (Figure 2), which is consistent with these saponins being triterpenoids [8,9].…”
Section: Effect Of Extraction Methods On Total Phenolic Content (Tpc)supporting
confidence: 75%
“…The finding that butanol and methanol were the best solvents for the extraction of the Gac seed saponins (Figure 2) is also consistent with previous studies. For example, butanol has been reported to be the solvent of choice for the extraction of saponins from the hull of Chenopodium quinoa seeds [39] while methanol has been used widely to extract saponins from a wide range of plant matrices [13,38]. Nonetheless, if the safety and economical characteristics of the solvent extraction system are a high priority, then water with MAE could be a reasonable choice for the extraction of Gac seed saponins.…”
Section: Effect Of Extraction Methods On the Total Saponin Content (Tsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Results are expressed as mean±SD (n=3) complex relationship among various natural antioxidant compounds. Antioxidants include diverse compositions, including polyphenols, vitamins, alkaloids, saponins, polysaccharides, and active peptides (O'Brien et al, 2006;Samaranayaka and Li-Chan, 2011;Carocho and Ferreira, 2013;Cheok et al, 2014;Zeng et al, 2014). Our preliminary study also found polysaccharides in C. cohnii (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…In North America, Burns et al (2011) showed the possibility of switchgrass grazing by steers and underlined the key role of stocking rates in summer dry period on switchgrass grassland for: i) ensuring an adequate pasture availability; ii) allowing a long-lasting of the sward. However, for the fresh consumption of switchgrass by ruminants, it is important to detect and assess the occurrence of anti-nutritional compounds like saponins (Lee et al, 2009;Cheok et al, 2014). Recently, switchgrass was studied also for a dual-purpose production, as forage and bioenergy crop, harvesting the herbage more often than once per year.…”
Section: Introductionmentioning
confidence: 99%